(untitled) (International Journal of Food and Nutritional Sciences, 2019)
A complex endocrine condition, polycystic ovarian syndrome (PCOS) affects 6% to 10% of women in their reproductive years. For overweight and obese girls with PCOS, dietary, exercise, and behavioral modifications seem to improve the problems related to metabolism and reproduction. The study was carried out on a obase PCOD girls of Guntur district, Andhra Pradesh